Successful Infection of Domestic Pigs by Ingestion of the European Soft Tick O. Erraticus That Fed on African Swine Fever Virus Infected Pig - Rémi Pereira De Oliveira; Evelyne Hutet; Maxime Duhayon; Jean-Marie Guionnet; Frédéric Paboeuf; Laurence Vial; Marie-Frédérique Le Potier (Viruses, 2020)
African swine fever is a highly lethal hemorrhagic fever of Suidae, threatening pig production globally. Suidae can be infected by different ways like ingestion of contaminated feed, direct contact with infected animals or fomites, and biting by infected soft tick bites. As already described, European soft ticks (Ornithodoros erraticus and Ornithodoros verrucosus) were not able to transmit African swine fever virus by biting pigs although these ticks maintained the infectious virus during several months; therefore, the possibility for pigs to become infected through the ingestion of infected ticks was questioned but not already explored. To determine if such oral ingestion is an alternative pathway of transmission, O. erraticus ticks were infected by blood-feeding on a viremic pig infected with the European African swine fever virus strain Georgia2007/1, then frozen at zero and two months post-engorgement, then after, were embedded in the food to pigs. Pig infection was successful, with superior efficiency with ticks frozen just after the infectious blood meal. These results confirmed the potential role of O. erraticus ticks as an ASFV reservoir and demonstrated the efficiency of non-conventional pathways of transmission.